Ndfip1 Prevents Rotenone-Induced Neurotoxicity and Upregulation of α-Synuclein in SH-SY5Y Cells - Liu, Xin; Qu, Le; Zhang, Na; Yu, Xiaoqi; Xiao, Zhixin; Song, Limei; Xie, Junxia; Xu, Huamin (Frontiers in Molecular Neuroscience, 2021)
Nedd4 family interacting protein 1 (Ndfip1) is an adaptor of Nedd4-family ubiquitin ligases. Experimental results showed that Ndfip1 had a potential neuroprotective effect in neurology diseases. However, the neuroprotective effect and the underlying mechanisms of Ndfip1 in Parkinson's disease (PD) have not yet been fully elucidated. Therefore, in this study, we explored the neuroprotective effect of Ndfip1 against mitochondrial complex I inhibitor rotenone in a human dopaminergic neuroblastoma SH-SY5Y cell line and further elucidated its possible underlying mechanisms. Our results showed that rotenone could induce the up-regulation of α-synuclein (α-syn) in both mRNA and protein levels. The expression of Ndfip1 decreased at 24 hrs after rotenone treatment. Further study showed that high expression of Ndfip1 could protect SH-SY5Y cells against rotenone-induced neurotoxicity and antagonize the rotenone-induced increase in α-syn protein levels. In addition, high expression of Ndfip1 inhibited rotenone-induced increase in the protein levels of caspase-3 and decrease in tyrosine hydroxylase (TH). Further study showed that Ndfip1 did not affect the protein expression of iron regulatory protein 1 (IRP1), transferrin receptor 1 (TfR1), while antagonized the increase in protein levels of P62 and ferritin L caused by rotenone. Our findings provide specific identification of Ndfip1 proteins to inhibit the increase of α-syn in rotenone-induced SH-SY5Y cells. Ndfip1 might be a new theoretical drug target for the prevention and treatment of PD.